Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

Exploring the molecular differentiation of sex chromosomes in Anastrepha fraterculus sp. 1 using comparative genomic hybridization (CGH) - M. Cecilia Giardini; Fabián H. Milla; Claudia A. Conte; Silvia B. Lanzavecchia; Mariela Nieves (Molecular Biology Reports, 2025)

A Chromosome Inversion Creates a Supergene for Sex and Colour in Lake Malawi Cichlids - Kristen A. Behrens; Soumya Jailwala; Frances E. Clark; Anne C. Meyer; Nikesh M. Kumar; Adrianus F. Konings; Reade B. Roberts; Matthew A. Conte; Jeffrey T. Streelman; Patrick T. McGrath; Thomas D. Kocher (Molecular Ecology, 2025)
Cichlid fishes have the highest rates of evolutionary turnover of sex chromosomes among vertebrates. Many large structural polymorphisms in the radiation of cichlids in Lake Malawi are associated with sex chromosomes and may also carry adaptive variation. Here, we investigate the structure and evolutionary history of an inversion polymorphism that includes both a ZW sex locus and an orange‐blotch colour polymorphism in the rock‐dwelling cichlid fishes of Lake Malawi. We use long‐read sequencing to characterise the sequence and breakpoints of the inversion. We quantify allele frequency differences across the inversion in population samples of the genera Metriaclima and Labeotropheus . We also examine expression differences of genes in the inversion. The simple inversion spans 7 Mb and is flanked by CACTA transposons that may have catalysed the rearrangement. The region includes ~600 genes, several of which show large differences in expression. Some of these genes are candidates for the sex and colour phenotypes. This inversion is an accessible model system for studying the role of structural polymorphisms and sex chromosome turnover in the adaptive radiation of cichlids in the lakes of East Africa.

SPORA, a new silver phosphate precipitation protocol for oxygen isotope analysis of small, organic-rich bioapatite samples - Gabriele Larocca Conte; Lauren E. Lopes; Aric H. Mine; Robin B. Trayler; Sora L. Kim (Chemical Geology, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

The aquatic particle number quandary - Alexander B. Bochdansky; Huanqing Huang; Maureen H. Conte (Frontiers in Marine Science, 2022)
Optical surveys of aquatic particles and their particle size spectra have become important tools in studies of light propagation in water, classification of water masses, and the dynamics of trophic interactions affecting particle aggregation and flux. Here, we demonstrate that typical settings used in image analysis vastly underestimate particle numbers due to the particle – gel continuum. Applying a wide range of threshold values to change the sensitivity of our detection system, we show that macrogels cannot be separated from more dense particles, and that a true particle number per volume cannot be ascertained; only relative numbers in relation to a defined threshold value can be reported. A quandary thus presents itself between choosing a detection threshold low enough to accurately record orders of magnitude more particles on one hand or selecting a higher threshold to yield better image quality of plankton on the other. By observing the dynamics of coagulation and dissolution steps unique to cation-bridged gels abundant in aquatic systems, we find naturally occurring gels, and microscopic particles attached to them, to cause the ill-defined particle numbers. In contrast, the slopes in particle number spectra remained largely unaffected by varying sensitivity settings of the image analysis. The inclusion of fainter particles that are not typically captured by imaging systems provides a window into the true microscale spatial heterogeneity at scales relevant to small plankton organisms and processes that are dependent on particle density such as surface-associated chemical reactions as well as particle coagulation and aggregation dynamics.

Disrupting mating of Lobesia botrana using sex pheromone aerosol devices - Andrea Lucchi; Paolo Sambado; Anna B. Juan Royo; Bruno Bagnoli; Giuseppe Conte; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

In situ remediation of contaminated marinesediment: an overview - G. Lofrano; G. Libralato; D. Minetto; S. De Gisi; F. Todaro; B. Conte; D. Calabrò; L. Quatraro; M. Notarnicola (Environmental Science and Pollution Research, 2017)

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

Great cormorant predation on Cisalpine pike: a conservation conflict - Giovanni B. Delmastro; Giovanni Boano; Paolo Lo Conte; Stefano Fenoglio (European Journal of Wildlife Research, 2015)

Redox state of subcontinental lithospheric mantle and relationships with metasomatism: insights from spinel peridotites from northern Victoria Land (Antarctica) - Cristina Perinelli; Giovanni B. Andreozzi; Aida M. Conte; Roberta Oberti; Pietro Armienti (Contributions to Mineralogy and Petrology, 2012)

An integrated database on ticks and tick-borne zoonoses in the tropics and subtropics with special reference to developing and emerging countries - Umberto Vesco; Nataša Knap; Marcelo B. Labruna; Tatjana Avšič-Županc; Agustín Estrada-Peña; Alberto A. Guglielmone; Gervasio H. Bechara; Arona Gueye; Andras Lakos; Anna Grindatto; Valeria Conte; Daniele De Meneghi (Experimental and Applied Acarology, 2011)

Potential allelopathic activity of Sideritis italica (Miller) Greuter et Burdet essential oil - A. Basile; R. C. Cobianchi; D. Rigano; F. Senatore; M. Bruno; S. Rosselli; B. Conte; S. Sorbo (Plant Biosystems, 2011)

Antioxidant activity in extracts from Leptodictyum riparium (Bryophyta), stressed by heavy metals, heat shock, and salinity - A. Basile; S. Sorbo; B. Conte; B. Golia; S. Montanari; R. Castaldo Cobianchi; S. Esposito (Plant Biosystems, 2011)

Expression Profile and Distribution of Efhc1 Gene Transcript During Rodent Brain Development - Fábio F. Conte; Patrícia A. O. Ribeiro; Rafael B. Marchesini; Vinícius D. B. Pascoal; Joelcimar M. Silva; Amanda R. Oliveira; Rovílson Gilioli; Lourenço Sbragia; Jackson C. Bittencourt; Iscia Lopes-Cendes (Journal of Molecular Neuroscience, 2009)

Organochlorine pesticides and polychlorinated biphenyl residues in reared and wild Dicentrarchus labrax from the Mediterranean Sea (Sicily, Italy) - V. Lo Turco; G. Di Bella; L. La Pera; F. Conte; B. Macrí; G. mo Dugo (Environmental Monitoring and Assessment, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Topiramate and cortical excitability in humans: a study with repetitive transcranial magnetic stimulation - M. Inghilleri; F. Gilio; A. Conte; V. Frasca; C. Marini Bettolo; E. Iacovelli; B. Gregori; M. Prencipe; A. Berardelli (Experimental Brain Research, 2006)

Effects of repetitive transcranial magnetic stimulation in a patient with fixation-off sensitivity - O. Mecarelli; B. Gregori; F. Gilio; A. Conte; V. Frasca; N. Accornero; M. Inghilleri (Experimental Brain Research, 2006)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Molecular and carbon isotopic composition of leaf wax in vegetation and aerosols in a northern prairie ecosystem - Maureen H. Conte; John C. Weber; Peter J. Carlson; Lawrence B. Flanagan (Oecologia, 2003)